2021
DOI: 10.1007/s11571-021-09702-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-additive activity modulation during a decision making task involving tactic selection

Abstract: Human brain imaging has revealed that stimulus-induced activity does generally not simply add to the pre-stimulus activity, but rather builds in a non-additive way on this activity. Here we investigate this subject at the single neuron level and address the question whether and to what extent a strong form of non-additivity where activity drops post-cue is present in different areas of monkey cortex, including prefrontal and agranular frontal areas, during a perceptual decision making task involving action and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Such a non-additive pre-stimulus-stimulus interaction is indeed confirmed by recent studies in fMRI [ 52 ], EEG/MEG [ 53 , 55 , 83 , 84 ], and cellular recordings [ 85 ]. The pre-stimulus activity provides a temporo-spatial context by means of which it can strongly shape the activity that the external input or stimulus can (or cannot) elicit, that is, stimulus-induced activity: the input effects are not simply added to the ongoing activity ( Figure 2 ).…”
Section: Neuronal Mechanisms—from Pre-stimulus To Stimulus-induced Ac...supporting
confidence: 60%
See 2 more Smart Citations
“…Such a non-additive pre-stimulus-stimulus interaction is indeed confirmed by recent studies in fMRI [ 52 ], EEG/MEG [ 53 , 55 , 83 , 84 ], and cellular recordings [ 85 ]. The pre-stimulus activity provides a temporo-spatial context by means of which it can strongly shape the activity that the external input or stimulus can (or cannot) elicit, that is, stimulus-induced activity: the input effects are not simply added to the ongoing activity ( Figure 2 ).…”
Section: Neuronal Mechanisms—from Pre-stimulus To Stimulus-induced Ac...supporting
confidence: 60%
“…How can we measure the impact of pre-stimulus activity during post-stimulus activity? One way is to measure trial-to-trial variability (TTV) that can be observed at both the levels of cellular and regional-systemic activity [ 78 , 85 , 86 , 87 , 88 ]. TTV measures the variation in the amplitude across different trials of one and the same stimulus.…”
Section: Neuronal Mechanisms—from Pre-stimulus To Stimulus-induced Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 52 Rather, these results suggest that the anatomical differences in these types of timescales are governed by different combinations of factors that can depend on cognitive and neural context. 53 That said, there is increasing evidence that prestimulus activity can influence poststimulus activity on a trial-by-trial basis, 54 , 55 , 56 including a prior study from our group using a subset of the data presented here. 55 The results here do not contradict these prior observations, as this study examines anatomical differences in mean dynamics, not trial-by-trial relationships.…”
Section: Discussionmentioning
confidence: 90%